Karakteristik fisiko kimia dan sensoris patty burger ikan patin dengan bahan pengisi pati jagung - Emma Riftyan; Suci Rahmayani; Dewi Fortuna Ayu (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Patty burger is one of the fast foods favored by the public, both children and adults. Consuming burgers for a long time can cause obesity, so other protein alternatives are sought, namely catfish as a substitute for beef. The purpose of this study is to obtain the best ratio of catfish and corn starch in making burger patties on physical, chemical, and sensory properties that meet Indonesian National Standard 8503-2018. The research method used a randomized design complete with four treatments and four repeats so that 16 experimental units were obtained. The treatment in this study was a comparison of the combination of catfish meat and corn starch, namely PM1 (85: 0), PM2 (80:5), PM3 (75:10), and PM4 (70:15). The data obtained were statistically analyzed using the ANOVA test and continued with Duncan's new multiple range test at the level of 5 %. The results showed that the ratio of catfish meat and corn starch had a significant effect on physical, chemical, and descriptive and hedonic sensory assessments except for color parameters. The burger patty treatment chosen is PM2 (80:5) which meets SNI 8503-2018. PM2 treatment is chosen based on the formulation of burger meat on the market which generally uses fillers in its manufacture. PM2 burger patty (80:5) has met SNI 7758-2013 standards with fat and protein content of 4.88 % and 13.27 % respectively. The burger patty from PM2 has a hardness value of 13.98 N and a moisture content of 66.01 %. The PM2 burger patty is slightly brownish on the outside but brownish white on the inside, has a slight catfish smell, a slight catfish flavor, and a chewy texture.